Numerical investigation of flow distribution and heat transfer of hydrocarbon fuel in regenerative cooling panel. (5th April 2016) - Chen, Yu; Wang, Yu; Bao, Zewei; Zhang, Qiyi; Li, Xiang-Yuan
Highlights: A three dimensional CFD simulation of regenerative cooling panel was conducted. Pressure field in manifold was analyzed to explain the flow distribution. Branch throttle was adopted to eliminate the difference of flow rate. Subcritical and supercritical flow distribution of hydrocarbon fuel was simulated. Temperature difference on the surface of cooling panel was analyzed. Abstract: To study the flow and heat transfer characteristics of hydrocarbon fuel in parallel branch channels of regenerate cooling panel in scramjet engine, a three-dimensional model with a blockage structure set in downstream channel was investigated numerically. The influences of downstream blockage on pressure field and flow distribution were analyzed in detail. The results indicated that transverse pressure gradient and difference of pressure drop at inlet of branch channels directly caused non-uniform distribution of mass flow rate. To eliminate the difference of flow distribution, branch throttle was carried out, and the characteristics of pressure drop produced by throttle were discussed. Simultaneously, flow distributions with branch throttle at subcritical and supercritical temperature region were presented. The changes of wall temperature as a result of flow rate distribution were described. The results demonstrated that throttle structure at inlet of each branch channel was able to restrain the difference of mass flow rate at different temperature region effectively and avoid local overheating.